China's protective policy towards North Korea. - Ho, Vincent Guan Qing. (2013)
China has been enjoying mutual and unique relationship with North Korea since the time of the Cold War era. China’s policies towards North Korea have been determined by its prime interests in the Korean Peninsula. According to the analysts, this helps China ensures its peaceful and stable position and secure the border with North Korea. In attaining these interests, China has managed to change the situation on the peninsula and its relationship with both Koreas. China provides the policy which is based on the need to maintain the status quo while seeking to avoid any kind of war.